KOMUNIKASI ANAK BROKEN HOME PADA LINGKUNGAN MASYARAKAT KECAMATAN BATANG SERANGAN KABUPATEN LANGKAT - Widya Putri Br Harahap; Sori Monang; Indira Fatra Deni (Lafadz Jaya Publisher, 2023)
This study aims to determine how the communication of broken home children in the community environment of Batang Serangan sub-district, Langkat Regency. This research uses descriptive qualitative research methods. The theory used in this research is Self Discloser Theory. Data collection techniques used are observation, interviews and documentation. Data analysis techniques in this study are data reduction, data presentation, and conclusion drawing. The conclusion in this study found that self-disclosure in interpersonal communication between broken home children and the surrounding community has a different depth of self-disclosure. The relationship between broken home children and the surrounding community is close, because most broken home children are willing to disclose information that is feeling.